Perilous Work Zones: Unveiling the Factors Influencing Health and Safety Risks in Tanzania's Informal Construction Sites - Mwemezi, Benson Rugalema; Kikwasi, Geraldine J.; Phoya, Sarah (University of Dar es Salaam Library Journal, 2023)
Informal construction (IC) emerged after the Second World War. Informal economies have largely led to it. IC comprises individuals conducting construction activities that are unregulated despite their economic contribution. IC faces health and safety risks (HSR), but little has been investigated on the factors influencing HSR in IC. This study identified and ranked the factors influencing HSRs in the IC sites (ICS) in Tanzania. Data was collected from 304 mason workers (MW) in ICS through questionnaires based on 24 factors derived from the literature. The study employed the quantitative method. Descriptive and inferential statistics were used for ranking and measuring the significance of factors. Findings revealed that lack of information and knowledge about safety rules, lack of awareness of risk management process and lack of framework and procedures were the significant factors highly influencing informal construction. Conversely, the lack of safety gear, drug abuse on-site and negligence have insignificant effects on informal construction. Moreover, the nature and physical layout of construction sites, labourers working in close proximity/overcrowded sites, and poor construction material arrangements were not significant factors. The study provides insight into the factors influencing HSR in informal construction. This study provides a baseline for developing an empirically grounded health and safety framework. The study will therefore pinpoint systematic HSR management procedures for improving HSR management in IC. Overall, the findings address the Sustainable Development Goals (SDG) 2030 Agenda Numbers 3 and 11, which aim to establish good health and well-being and mobilize sustainable cities and communities.